Plan de negocios para la elaboración de pulpas de frutas combinadas con propiedades naturales del Asia para la ciudad de Quito - Ponce Jácome, José Luis (2017)
This document provides all the relevant information regarding the findings obtained during the study of the fruit pulp and preserved food industry. Starting from a detailed investigation of the internal and external environments, in order to be able to find and consider all possible alternatives and signs of opportunity that lead to the appropriate decision to undertake this project as the central theme of this business plan. Considering the main factors that represent a firm idea that serves as a foundation to start the implementation of a company that produces and commercializes pulp fruits through strategic partners that work in sales of processed foods. The goal of the concept is to elaborate a complete and structured system of added value for the manufacture of fruit pulps that are combined with natural properties extracted from plants of Asian origin to be offered to the people of the city of Quito. The developed idea begins with the elaboration and implementation of a whole procedure that provides an ideal support for the manufacture of refrigerated fruit pulps. The supply of raw materials, production and sale of final product, will be supported by a special counselling that will allow it to be recognized as a different kind of food option and to draw the attention of the final consumers of the target market. The initial investment would be of USD 116.974, which would have an individual capital of USD 58.487. During the first 5 years of the project, it will be viable since it generates a net present value of USD 195.379, a profitability index of 2.67 and an internal rate of return (IRR) of 39.60% for the project. The investor generates a value of USD 147.022, a profitability of 4.68 and IRR of 52.06%.